ANALISIS KEMAMPUAN SISWA SMP DI TIMOR DALAM MENYELESAIKAN SOAL BERBENTUK HIGHER ORDER THINGKING MATERI ALJABAR - Oktovianus Mamoh; Faustinus Luan; Hendrika Bete (Prodi Pendidikan Matematika FKIP Universitas Madura, 2020)
The development of the world globally in various fields of life has demanded intense competition. Therefore, every individual who inhabits this world needs to have certain competencies in order to be able to compete in this globalization era. Hence, each individual must be able to think at a high level (higher order thingking / HOT) especifically on math subjects. But the problems that occur, there are still many students who have difficulty in solving the problems in the form of higher order thinking (HOT) so that they have not been able to compete globally. To overcome this problem the researcher carried out a higher order thingking analysis on Algebraic material. This study aims at describing the analysis of higher order terms in Algebraic material. The method used were a test and interview of 3 informants in six schools based on students' levels of ability, namely high ability, moderate ability and low ability. The results showed that there were differences in solving HOT problems in students who had high, medium and low abilities.